CFD simulation of contaminant transportation in high-risk buildings using CONTAM - Nikolaou, Andreas; Michaelides, Michalis P. (My University, 2014)
In this work we study the problem of airborne contaminant transportation in high-risk buildings using CFD methods. The main contribution of this work is the design and evaluation of two building case studies using CONTAM coupled with the CFD0 Editor: (i) a conceptual office building with a large conference room surrounded by four smaller offices and (ii) the Pefkios Georgiades amphitheater which is a real building housed at the Cyprus University of Technology in Lemesos. For both case studies, a large number of scenarios were performed involving the transportation of a dangerous contaminant from various locations inside the building and recommendations were provided as to the number and locations of sensors that would guarantee prompt detection to ensure the safety of the people. A comparison of CFD to multi-zone and a study regarding the total computational time of CFD with respect to the grid size were also performed.
Keywords: CFD; CONTAM; Contaminant transportation; Critical infrastructure protection; High-risk buildings; Sensor placement